Methodological tools of assessing the formation of linguodidactic (special) competence in the conditions of transition to the 3++ FSES HE - Lyudmila A. Milovanova; Alina S. Karavaeva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article deals with the peculiarities of the modernized system of training of foreign language teachers to professional activity under the conditions of the 3++ FSES HE following the requirements of the professional standard of a teacher. The specifically developed methodological technology to determine the level of formation of the linguodidactic competence of future foreign language teachers is suggested. The model of professionally oriented (linguodidactic) task, presenting the correspondence of the task’s units, the levels of formation and the components of linguodidactic (special) competence, is introduced.